Access to Livelihood Capital and Food Security Status as Correlates to Empowerment Among Women on Irrigation Schemes in North-West Province, South Africa - Oladimeji Idowu Oladele (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
This paper examines the empowerment, access to livelihood capital, and food security status among women in irrigation Schemes in North-West Province, South Africa. A simple random sampling technique was used to select 84 women farmers. Data was obtained with a female empowerment agricultural index questionnaire and analyzed with frequency distribution, percentages, mean and standard deviation, and Chi-Square. The results on the indices of empowerment show that women are disempowered in the use of income and access to productive capital and credit, but are empowered in leadership and decision-making. The Chi-square analysis reveals that significant relationships exist between levels of empowerment, livelihood capital, and food security. The paper concludes that there is a need to modify intervention programs if empowerment is to be attained.